El debido proceso y la seguridad jurídica en el informe de sobreprecio determinado por la Contraloría General del Estado. - Fiallo Viteri, Rodrigo Alejandro (2024)
With the reform to the Comprehensive Organic Criminal Code, in force since February 17, 2021, in anti-corruption matters, the report on overpricing in public procurement is incorporated, which, for its determination, provides that the State Comptroller General's Office issues a report concluding evident and proven overpricing in the government audit, that is, a report that constitutes a procedural requirement for a criminal offense; The Ecuadorian legal system is hierarchical in accordance with articles 424 and 425 of the supreme norm, which is why the Constitution of the Republic of Ecuador prevails over any other norm of legal rank, in this sense, article 212 determines the powers of the State Comptroller General's Office, which in its paragraph 2, attributes to the control entity the determination of administrative and civil culpable responsibilities and indications of criminal liability, related to the aspects and procedures subject to its control, without prejudice to the functions that in this matter they are the responsibility of the State Attorney General's Office; Under these arguments, the purpose of this research is to contribute to legal development in the Republic of Ecuador, through the analysis and study of cases, on the verification of the overpricing report determined by the Comptroller General of the State and compliance with the rights to due process and legal security, carrying out a doctrinal, critical and legal study, focused on the overpricing report determined by the State Comptroller General's Office, provided in the Comprehensive Organic Penal Code; In the same way, it will be indicated whether due process and legal certainty were guaranteed in the overpricing report determined by the State Comptroller General's Office, and, if applicable, a reform or expulsion of article 294.1 of the Comprehensive Organic Criminal Code, with the purpose of guaranteeing constitutional rights.